(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Shelf life means the time period during which the potency of a drug remains unaffected from environmental factors or microbial contamination. Nowadays diverse procedures of making powder are available which affect on shelf life of them. Ocimum sanctum L. is most common household herb in Indian subcontinent. Hence, the present study is aimed to develop analytical profile of Ocimum sanctum L. leaves powder by classical and lyophilized method and compare the stability of both the samples. Materials and Methods: Ocimum sanctum L. leaves powder was prepared by two different drying methods and accelerated stability study was conducted as per ICH guideline Q1A (R2). Physicochemical analysis was repeated at interval of 0, 1, 3 and 6 months. Organoleptic parameters, microbial limits and heavy-metal analysis were observed at specific intervals. Result and Discussion: No significant changes were observed in organoleptic characters of both the samples up to storage of 6 months at accelerated condition. The values of physicochemical parameters of both the samples were within the prescribed limit specified in Ayurvedic Pharmacopeia of India. Results of Microbiological limit test were also below the limit and considerably decreased at specific intervals. Heavy metals namely arsenic, cadmium and mercury were not detected and lead was present below detectable limits. Conclusion: Analysis revealed that the classically prepared powder has better shelf life (3.08 years) than lyophilized powder (2.70 years) and also provides the modest and effective ways for optimal Eugenol extraction in accelerated conditions.